Preparation of polyacrylic latex with external crosslinking and its effect on the pressure-sensitive properties. Issue 4 (1st October 2020) - Meng, Weixiao; Gao, Wenshu; Zhu, Lin; Liu, Mengyu; Qu, Xiongwei
ABSTRACT: A series of external crosslinked polyacrylic latexes with the same particle sizes were synthesized at a solid content of 50 wt% via semi-continuous emulsion polymerization with diacetone acrylamide (DAAM) and adipic acid dihydrazide (ADH) as the external-crosslinking agents, named as poly(BA- co -MAA- co -DAAM)-ADH, PBMD-A. The effects of crosslinking agent content on the emulsion polymerization, molecular structure, and molecular motion were investigated by means of gravimetric analysis, dynamic light scattering (DLS) and dynamic mechanical analysis (DMA). The results showed that the crosslinking agent content had no significant effect on the polymerization process. The overall conversions of monomers with different crosslinking agent contents were high, and the latex particles grew in a spherical shape without generating secondary particles during the growth process. With the increase of the crosslinking agent content, the gel content, glass transition temperature, and storage modulus of the PBMD-A increased. The adhesive properties, including tack force, peel force and shear resistance of the PBMD-A products were evaluated using the FINAT test methods. This paper provided a facile and ecological method to rapidly increase rapidly the shear resistance and kept other adhesion performance for polyacrylic pressure-sensitive adhesives (PSAs) with addition of a small amount of external-crosslinking agent.